2018
DOI: 10.3390/rs10101502
|View full text |Cite
|
Sign up to set email alerts
|

Using Window Regression to Gap-Fill Landsat ETM+ Post SLC-Off Data

Abstract: The continued development of algorithms using multitemporal Landsat data creates opportunities to develop and adapt imputation algorithms to improve the quality of that data as part of preprocessing. One example is de-striping Enhanced Thematic Mapper Plus (ETM+, Landsat 7) images acquired after the Scan Line Corrector failure in 2003. In this study, we apply window regression, an algorithm that was originally designed to impute low-quality Moderate Resolution Imaging Spectroradiometer (MODIS) data, to Landsat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Figure 13b displays the lava flow emitted by the Eyjafjallajökull volcano on 3 April 2010 and generated by an intense effusive eruption which started the previous month after about two centuries of quiescence, previously investigated from space by means of infrared MODIS data [75]. It should be noted that, despite the striping in Landsat-7 ETM+ imagery (e.g., [76]), the analyzed time series (from 1999 to 2011) did not reveal any false detection (see quiescence periods correctly marked by the tool before and after the end of eruption). Thus, the NHI tool seems to perform well in using also TM/ETM+ data, although the impact of other issues (e.g., oversaturation effects [77]) needs to be better assessed.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Figure 13b displays the lava flow emitted by the Eyjafjallajökull volcano on 3 April 2010 and generated by an intense effusive eruption which started the previous month after about two centuries of quiescence, previously investigated from space by means of infrared MODIS data [75]. It should be noted that, despite the striping in Landsat-7 ETM+ imagery (e.g., [76]), the analyzed time series (from 1999 to 2011) did not reveal any false detection (see quiescence periods correctly marked by the tool before and after the end of eruption). Thus, the NHI tool seems to perform well in using also TM/ETM+ data, although the impact of other issues (e.g., oversaturation effects [77]) needs to be better assessed.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Research to assess and consider more sophisticated processing using the ARD is ongoing, including correction for bi-directional reflectance and topographic effects, gap-filling and improved cloud masking [23,28,41,42]. A recommendation of this study is to improve the Landsat geolocation processing.…”
Section: Discussionmentioning
confidence: 99%
“…Brooks et al [16] applied a window regression method that was originally developed to impute low-quality moderate resolution imaging spectroradiometer (MODIS) to Landsat ARD between 2014 and 2016 to gap-fill Landsat ETM+ SLC-off data. For the five study areas, root mean square error derived from the observed reflectance ranged from 3.7%-7.6% for different spectral bands, and it outperformed other algorithms such as the neighborhood similar pixel interpolator gap-filling algorithm.…”
Section: Science Of Landsat Ard In This Special Issuementioning
confidence: 99%